2011
DOI: 10.1186/1476-069x-10-43
|View full text |Cite
|
Sign up to set email alerts
|

Natural radionuclide of Po210 in the edible seafood affected by coal-fired power plant industry in Kapar coastal area of Malaysia

Abstract: BackgroundPo210 can be accumulated in various environmental materials, including marine organisms, and contributes to the dose of natural radiation in seafood. The concentration of this radionuclide in the marine environment can be influenced by the operation of a coal burning power plant but existing studies regarding this issue are not well documented. Therefore, the aim of this study was to estimate the Po210 concentration level in marine organisms from the coastal area of Kapar, Malaysia which is very near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 32 publications
1
23
0
1
Order By: Relevance
“…Regions containing industries that release NORM can also influence 210 Po in molluscs. Water in the vicinity of a coal powered power plant in Malaysia was noted by the authors as having higher 210 Po activity than other locations around the coast (Alam and Mohamed, 2011).…”
Section: Polonium Analysismentioning
confidence: 98%
“…Regions containing industries that release NORM can also influence 210 Po in molluscs. Water in the vicinity of a coal powered power plant in Malaysia was noted by the authors as having higher 210 Po activity than other locations around the coast (Alam and Mohamed, 2011).…”
Section: Polonium Analysismentioning
confidence: 98%
“…Ikan dan hasil laut merupakan sumber makanan yang penting di pelbagai tempat di dunia dan mempunyai potensi besar sebagai sumber protein berharga bagi kebanyakan negara membangun (Young et al 2002). Malaysia dianggap antara pengguna makanan laut yang paling tinggi di rantau Asia Tenggara mengikut tempoh pengambilan per kapita dan peratusan protein (Alam & Mohamed 2011).…”
Section: Pengenalanunclassified
“…Coal is the second-largest energy source, playing a paramount role in generating electricity by contributing up to 39% in global production (Alam & Mohamed, 2011). In China, coal plays a much bigger role in electricity generation by accounting for over 75% of the nation's electricity capacity (Chuangao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The contamination of 210 Po in ocean can be spread to seafood through food chain, and eventually affect human being. Lubna et al estimated the 210 Po concentration level in marine organisms from the coastal area close to a CFP and assessed its impact on seafood consumers (Alam, 2016;Alam & Mohamed, 2011, 2018. They found that the average activity observed in the dissolved phase is higher than that of other places in the same country.…”
Section: Introductionmentioning
confidence: 99%